Parkinsonism in a young adult after ventriculoperitoneal shunt procedure for tri ventricular obstructive hydrocephalus – A case report - Mahathy SU; Selvakumar CJ; Hempragadish JG (Asian Journal of Medical Sciences, 2024)
This case report centers on a 19-year-old male diagnosed with tri-ventricular obstructive hydrocephalus due to aqueductal stenosis. Following a right ventriculoperitoneal (VP) shunt procedure, the patient initially exhibited marked improvement but later developed Parkinsonian symptoms. Extensive investigations meticulously ruled out shunt malfunction and phenytoin toxicity. The suspicion of Parkinsonism secondary to VP shunt emerged, leading to the initiation of anti-Parkinsonian medications. The patient underwent a personalized treatment regimen with anti-Parkinsonian drugs, which yielded substantial clinical improvement. This case report underscores the importance of identifying unusual neurological presentations post-VP shunt. The critical role of early diagnosis and precise pharmacological intervention in the patient’s recovery cannot be overstated, and it emphasizes the potential for rare complications like post-shunt Parkinsonism.